2-Year Results from the GO-RAISE Trial - Rizzo, Toni (MD Conference Express, 2012)
The Multicenter Randomized, Double-blind, Placebo-controlled Trial of Golimumab, a Fully Human Anti-TNFa Monoclonal Antibody, Administered Subcutaneously, in Subjects with Active Ankylosing Spondylitis trial [GO RAISE] evaluated the efficacy and safety of golimumab in patients with active ankylosing spondylitis (AS). Objectives of this analysis were to assess AS Disease Activity Score major improvement and inactive disease and their association with improvements in Health Related Quality of Life, and work productivity in patients with AS after 2 years of treatment with golimumab.